Investigation on the performance of LDDS using biomass-based wood shaving as the packing material. Issue 7 (9th August 2022) - Suranjan Salins, Sampath; Reddy, S.V. Kota; Kumar, Shiva; Kumar, Sreejith Sanal
ABSTRACT: Current work emphasises the counter flow liquid desiccant dehumidification system (LDDS) that uses a novel fabricated packing frame filled with biomass-based wood shaving material which used Calcium chloride as liquid desiccant. Experiments are carried out by varying mass flow rate, temperature, and concentration. Various dehumidification performance parameters such as moisture removal rate (MRR), Coefficient of performance, Dehumidification efficiency, mass transfer coefficient, change in humidity, and air temperature are studied. System gave an increased dehumidification performance at high concentration and low inlet temperature of the desiccant. Results revealed that when the flow rate is maintained between 0.5 and 0.55 Litres per minute, optimised performance parameters like energy consumption, MRR, COP, dehumidification efficiency are 662 Watts, 0.57 g/s, 2.7, 54% correspondingly.